Highly Efficient and Broadband Hybrid Photodetector Based on 2-D Layered Graphene/CTS Quantum Dots - Yadav S.M.; Pandey A. (My University, 2025)
This paper reports the fabrication of a broadband near-infrared response (vis-NIR) photodetector (PD) using Cu2SnS3 (CTS) quantum dots (QDs) as photoactive semiconductor material and graphene as a carrier transport medium. The QDs of earth abundant, nontoxic, and inexpensive CTS have been synthesized by solvothermal method, and the chemical vapor deposition (CVD) technique is used to synthesize few layers and monolayers of graphene. The fabricated CTS QDs/graphene/SiO2/Si PD demonstrated high values of responsivity (110.089 A/W), detectivity ( 1.25 × 1012 cm · Hz1/2 · W-1), and quantum efficiency (160.9) for broadband (vis-NIR) region due to high absorption coefficient of CTS QDs and very high mobility (200 000 cm2/V-s) of graphene. The time-response analysis of PD was also performed under vis-NIR and ON and OFF time were found to be 10.2 and 11.34 s. © 1963-2012 IEEE.